Sociology in Algeria: Readings in practice and thinking - Guenifa, Nora; Tali, Djamel (Al-Adab Journal, 2023)
This work is a serious attempt to provide a critical reading of the reality of sociology in Algeria. Especially since it employs the historical data that produced an Algerian sociology or sociology that carries a very different Algerian intellectual specificity from Arab intellectual practices, knowledge and a realistic given according to a political, socio-cultural and religious context. Its beginnings characterized an identity conflict between two groups present in same geographical sphere.As for the next stage, it was characterized by strong political and economic transformations with a multidimensional impact, most notably the failure of various development approaches, which led to political and economic shocks that resulted in societal crises. On the other hand, also closed academic intellectual issues for those working in the social field, which produced a limited sociological discourse that was unable to provide an explanation of many emerging phenomena in society, especially those related to societal sanctities and sexual taboos, and only consumed the ready cognitive and ideological mold.Through this scientific article, we will try to highlight the most important characteristic of the tasks of those working in the sociological field in thinking and practice over long periods of time, and with an analytical critical vision.